2003
DOI: 10.1002/ejoc.200300207
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Structures of Imidazole Analogues of Lissoclinum Cyclopeptides

Abstract: The syntheses of the cyclic peptides 3−7, which contain imidazole units in their backbones and resemble naturally occurring marine cyclopeptides such as westiellamide and ascidiacyclamide, are described. Structural investigations on the trimer 3 reveal a molecular triangle conformation with all lone pairs of the imidazole nitrogen atoms and the hydrogen atoms of the secondary amides directed to the center of the macrocycle. The structures of the tetramers 4 and 6 display distorted molecular square conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 66 publications
0
78
0
4
Order By: Relevance
“…The break-through in our own studies was the accessibility of a variety of ligands based on a modular synthesis which allowed the preparation of appreciable quantities of ligands in relatively short time, and with the possibility to tune their structures and flexibilities as well as the electronics of the donor groups via the type of heterocycle and the configuration of the macrocycle side-chain. 54,56,57,65,66,68 The other important factor, leading to a comprehensive account with respect to the coordination chemistry involved, is based on the combination of various spectroscopies (UV-vis-NIR, CD, MCD, ESI-MS, NMR, EPR, HYSCORE and ENDOR) with computational modeling (structure optimization and electronic structure calculation); thorough kinetic studies and thermodynamic analyses have started to appear and begin also to be combined with modeling approaches -in this area there still is important work ahead. Obvious next steps are similar sets of experiments with other metal ions and other (hydrolysis) reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The break-through in our own studies was the accessibility of a variety of ligands based on a modular synthesis which allowed the preparation of appreciable quantities of ligands in relatively short time, and with the possibility to tune their structures and flexibilities as well as the electronics of the donor groups via the type of heterocycle and the configuration of the macrocycle side-chain. 54,56,57,65,66,68 The other important factor, leading to a comprehensive account with respect to the coordination chemistry involved, is based on the combination of various spectroscopies (UV-vis-NIR, CD, MCD, ESI-MS, NMR, EPR, HYSCORE and ENDOR) with computational modeling (structure optimization and electronic structure calculation); thorough kinetic studies and thermodynamic analyses have started to appear and begin also to be combined with modeling approaches -in this area there still is important work ahead. Obvious next steps are similar sets of experiments with other metal ions and other (hydrolysis) reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis and characterization of the derivatives H 3 L 1 , H 3 L 2 , and H 3 L 3 have been described previously. [33,34] Compounds H 3 L wa and…”
Section: A C H T U N G T R E N N U N G (H 2 L)]mentioning
confidence: 99%
“…Recently, we were able to show that modified marine cyclopeptides, which are structurally similar to CTVs, can be synthesized in a few steps [19][20][21] . Structural investigations of modified marine cyclopeptides revealed that small-halogenated hydrocarbons, such as methylene chloride or chloroform, are enclosed into the solid [22][23][24] .…”
mentioning
confidence: 99%